Treatment of Moderate Sized Renal Pelvis Calculi: Stone Clearance Time Comparison of Extracorporeal Shock Wave Lithotripsy and Retrograde Intrarenal Surgery - Ercil, Hakan; Alma, Ergun; Bas, Okan; Sener, Nevzat Can; Vuruskan, Ediz; Kuyucu, Faruk; Unal, Umut; Gören, Mehmet Resit; Evliyaoglu, Yalcin (Urology Journal, 2016)
Purpose: To compare the stone clearance times in patients undergoing extracorporeal shock wave lithotripsy (SWL) or retrograde intrarenal surgery (RIRS) for single radiopaque renal pelvis stones 10-20 mm in size. The results of this study may guide urologists and patients and aid in selecting the optimal preoperative treatment. Materials and Methods: Between January 2013 and February 2015, we conducted a retrospective study and collected data from 333 patients treated with SWL (n = 172) or RIRS (n = 161). We included successfully treated patients with a single radiopaque renal pelvis stone 10-20 mm in size to calculate stone clearance times. Results: The average stone size for the SWL group was 14.62 ± 2.58 mm and 14.91 ± 2.92 mm for the RIRS group. The mean Hounsfield unit (HU) of the patients was 585.40 ± 158.39 HU in the SWL group and 567.74 ± 186.85 HU in the RIRS group. Following full fragmentation, the mean stone clearance time was 26.55 ± 9.71 days in the SWL group and 11.59 ± 7.01 days in the RIRS group (P < .001). Conclusion: One of the most overlooked parameters in urinary stone treatments is stone clearance. We believe this study will shed light for those who aim to conduct larger randomized prospective studies.